Pitting corrosion of 17-4PH stainless steel manufactured by laser beam melting. (June 2020) - Barroux, Adrien; Ducommun, Nadège; Nivet, Eric; Laffont, Lydia; Blanc, Christine
Graphical abstract: Highlights: Differences in composition and microstructure were observed between both MSSs. Pitting potential was more noble for laser beam melting (LBM) 17-4PH steel (MSS). NbC precipitates seemed to be detrimental for stable pitting corrosion resistance. LBM MSS was more susceptible to metastable pitting than the wrought MSS. Gas pores were assumed to influence the repassivation ability of the LBM MSS. Abstract: The pitting corrosion behaviour of a 17-4PH martensitic stainless steel (MSS) manufactured by power bed laser beam melting (LBM) was compared to that of a wrought MSS. More noble pitting potentials were measured for LBM samples, probably due to a smaller size of NbCs as compared to wrought MSS. The metastable pits were less numerous, but had a higher nucleation rate and longer life time for the LBM samples compared to the wrought MSS. This was explained by assuming a decrease in the repassivation ability of LBM samples due to small gas pores.